ANALISIS PERILAKU KONSUMEN DALAM PENGGUNAAN OVO SEBAGAI METODE PEMBAYARAN - Anggi Nur Iftitah; Miftakhul Jannah; Moh. Ilham (VARIABLE RESEARCH JOURNAL, 2024)
The aim of this research is to analyze consumer behavior in using OVO (One Vision One) as a digital payment method. OVO is a digital payment platform that is increasingly popular in Indonesia. The approach used in the research is a qualitative approach by conducting in-depth interviews and observations with a number of respondents who are active OVO users. The research results show that consumer behavior in using OVO is influenced by a number of factors. These factors include trust in OVO security, comfort in use, promotional offers, and social factors. Consumers tend to choose OVO as a payment method because they feel safe and comfortable with this platform. Apart from that, promotions and incentives offered by OVO also influence consumers' decisions to use it. Apart from that, this research also identifies changes in consumer behavior over time in using OVO. Some consumers were initially skeptical of digital payments but then became more accustomed and comfortable with using OVO. Shows that the adoption of digital payment technology such as OVO can change consumer behavior. This research provides valuable insights for companies operating in the digital payments sector, especially OVO, to understand their consumer behavior. By understanding the factors that influence OVO usage and changes in consumer behavior over time, companies can develop more effective strategies to market their products and increase consumer satisfaction.